2023
DOI: 10.3389/fcvm.2023.1113509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inspiratory muscle training in patients with hypertension: a meta-analysis

Abstract: ObjectiveTo explore the effects of inspiratory muscle training (IMT) on hypertension and provide guidance for its clinical application as an auxiliary approach.MethodsArticles published prior to July 2022 were searched in Cochrane Library, Web of Science, PubMed, Embase, CNKI, and Wanfang databases. Included were randomized controlled studies that used IMT to treat individuals with hypertension. The mean difference (MD) was computed using the Revman 5.4 software. In individuals with hypertension, the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…IMT has also shown good effectiveness regarding the reduction in respiratory complications due to stroke [5,45] However, it has not yet shown impact on quality of life and needs to be explored more [5,45,46]. While the intensity of IMT does not seem to be as important as the duration in the first 12 weeks of IMT for stroke and HF patients, the meta-analysis conducted by Zheng et al [4] suggested that low-intensity IMT is more effective on hypertension than moderate and high intensities. However, its effect on quality of life remains uncertain [47,48].…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…IMT has also shown good effectiveness regarding the reduction in respiratory complications due to stroke [5,45] However, it has not yet shown impact on quality of life and needs to be explored more [5,45,46]. While the intensity of IMT does not seem to be as important as the duration in the first 12 weeks of IMT for stroke and HF patients, the meta-analysis conducted by Zheng et al [4] suggested that low-intensity IMT is more effective on hypertension than moderate and high intensities. However, its effect on quality of life remains uncertain [47,48].…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…The same authors concluded that in patients with inspiratory muscle weakness and chronic heart failure, IMT improves limb blood flow under training in these populations. Moreover, in patients with hypertension, IMT can be a complementary strategy to reduce resting heart rate, pulse pressure, systolic and diastolic blood pressures [4]. In post-stroke patients, IMT increases pulmonary function and cardiopulmonary endurance and reduces pulmonary infection incidence in this population [5].…”
Section: Introductionmentioning
confidence: 99%
“…IMT reduces the blood pressure, heart rate, and pulse pressure in patients with hypertension [53]. IMT improves exercise capacity, pulmonary functions, and health-related quality of life in coronary artery disease patients with stable angina [54].…”
Section: Cardiovascular Diseasementioning
confidence: 99%